Pull out and creep behaviour of soil nailing - A Case Study / M.J. Md. Noor and M. F. Jamain - M.J., Md. Noor; M. F., Jamain (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
The use of soil nails for slope strengthening is one of the popular methods since 1980s due to the attractive benefits of simple and fast installation method to reinforce cut slope. Proper assessment of the soil nail behavior between the nails and the surrounding soil will contribute to the safe and economical design of the reinforced soil structure. At present, the safety factor is adapted to soil nailing design and analysis, however, some soil nailed slope, which are designed, in compliance to the slope guidelines end up with failure. For the current knowledge, there is limited information on the loss of the shaft friction in soil nailing due to creep and the research on the behavior of the soil nail is also limited. Hence, in order to provide additional information on the behavior of the conventional soil nailing system, the bore holes and pull out test data were collected from the various projects: 1) Cheras, Kuala Lumpur, 2) Penang Hill, Penang, and 3) Kajang, Selangor. This study is focused on the behavior of the soil nail under pull out test at various types of soils and different soil nails characteristics. The parameters measured are soil nail pull out resistance and displacement of soil nails under different loading. In addition, the creep behavior of the soil nail was a study based on the displacement under maintain period at maximum test load during the pullout test. The creep behavior of soil nail is causing the loss of tension in the soil nail and that affecting the performance of the engineered slope. For the study and result presented, it is clear that soil nail under certain types of soil, especially dry, poorly graded cohesionless soils or soil with high water table is creep susceptible and had a lower pull out resistance. Pull out test on soil nail installed in medium stiff clayey Silt and sandy Silt and socketed in rock is performing up to design expectation